Transmissão por insetos do complexo papaya meleira virus (PMeV e PMeV2) e prospecção e caracterização de uma fração da proteína estrutural do PMeV - Almeida, Joellington Marinho de (2024)
Papaya blight is a disease caused by a virus that can lead to a loss of productivity in Carica papaya orchards in producing countries such as Brazil, Mexico, Ecuador and Australia where the disease occurs. Infection of the plant causes burning of the tips of young leaves, spontaneous exudation of latex and spots on the fruit. The latex oxidizes in the presence of air, giving rise to a "honey-like" appearance, which together with other factors interferes with the commercial acceptance of the fruit. However, the vector that transmits the papaya late blight disease is still unknown in all producing countries. Studies carried out by various research groups have pointed to the leafhopper as a potential disseminator of the disease, in addition to the relationship with fungi, seeds and mechanical transmission. In Brazil, it is caused by the viral complex papaya meleira virus (PMeV) and papaya meleira virus 2 (PMeV2), and the coexistence of the two viruses has proven that PMeV2 is encapsidated by PMeV, and it is known that PMeV has two ORFs responsible for encoding structural proteins that make up the capsid (ORF1) and a putative RdRp protein (ORF2). Knowing that the structural proteins of PMeV are responsible for encapsidating the two genetic materials, the use of the expression of a recombinant protein fraction of the capsid protein (CP) of PMeV could become viable in the development of rapid tests, identification of viral particles in different locations of the plant and potential application in studies of virus-plant-vector transmission. In this study, we developed material on understanding the viral transmission of the papaya meleira virus complex by insects using the available literature and the prospecting and characterization of a fraction (p441) of the PMeV structural protein. The p441 fraction of the PMeV capsid protein was expressed in E. coli BL21(DE3) and extracted from the SDS-PAGE gel. The protein fraction was expressed at four different times (30 minutes, 1 hour, 2 hours and 4 hours) to check which would correspond to its highest production and its extracted fraction was used to produce polyclonal antibodies. Based on the available sequence, an in silico characterization was carried out to determine ab initio secondary and tertiary structure models, physicochemical parameters and the prediction of immunogenic peptides that could be identified in its primary sequence. The results obtained open up possibilities for the design of tests that are effective in detecting PMeV, based on observations made about the protein structure of the p441 fraction as being a stable protein with low thermal mobility. In addition, 18 peptides found on its surface have been shown to be capable of triggering an immune response and to be a region that can be used to produce antibodies that can be applied in future studies to locate the virus in different parts of the plant. Finally, it was found that the conditions of expression in a time of 4 hours obtained the best response, generating protein concentrations of around 633 to 923 mg/mL verified after SDS-PAGE gel extraction